IMPLEMENTASI GAME BERBASIS WORDWALL DALAM PEMBELAJARAN DI SEKOLAH DASAR NEGERI 28 BANDAR BARU: Implementasi Pembelajaran dengan Game Berbasis Wordwall dalam Kegiatan Pengabdian di Sekolah Dasar Negeri 28 Bandar Baru, Kabupaten Pidie Jaya - Rambang Muharramsyah; Yuliana Yuliana; Muhibbudin Muhibbudin; Teuku Armansyah; Nadia Aldyza (LPPM Universitas Almuslim, 2026)
This community service initiative focused on implementing Wordwall-based games as an interactive learning medium at SD Negeri 28 Bandar Baru, Pidie Jaya Regency. The participants included 28 fourth-grade students and three classroom teachers who utilized these games in their instruction. By leveraging the Wordwall platform, teachers were able to create engaging and enjoyable learning activities tailored to the curriculum. The implemented methods included quizzes, matching exercises, word scrambles, and